Evaluation of Services to Domestic Minor Victims of Human Trafficking; 2011-2013 - Gibbs, Deborah ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. This study was a process evaluation of three programs funded by the U.S. Department of Justice (DOJ) Office for Victims of Crime (OVC) to identify and provide services to victims of sex and labor trafficking who are U.S citizens and lawful permanent residents (LPR) under the age of 18. The three programs evaluated in this study were: The Standing Against Global Exploitation Everywhere (SAGE) Project The Salvation Army Trafficking Outreach Program and Intervention Techniques (STOP-IT) program The Streetwork Project at Safe Horizon The goals of the evaluation were to document program implementation in the three programs, identify promising practices for service delivery programs, and inform delivery of current and future efforts by the programs to serve this population. The evaluation examined young people served by the programs, their service needs and services delivered by the programs, the experiences of young people and staff with the programs, and programs' efforts to strengthen community response to trafficked youth.